2004
DOI: 10.1111/j.1439-0418.2004.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

The fruit fly PUB: a phagostimulation unit bioassay system to quantitatively measure ingestion of baits by individual flies

Abstract: A bioassay to investigate quantitative phagostimulation and ingestion physiology of baits on individual fruit flies is presented. The study was undertaken using two fruit fly species: the Mediterranean fruit fly (Ceratitis capitata), a cosmopolitan insect pest, and the Ethiopian fruit fly (Dacus ciliatus), a quarantine insect in Israel. Our model bait suspension included spinosad as the toxic agent, and 1% yeast hydrolysate with 10% sucrose as phagostimulant. A preliminary toxicology study showed that the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…The test suspension was offered to the flies at a concentration of 8 mg protein mL −1 , while controls were fed with the desalted Adamek's liquid protein fraction. In either assay, the ingested volumes in controls and treatments were calculated by measuring the suspension remaining in each microtube cap 26. Every day for a 5 day period before refilling the caps, the suspension remaining in each cap was removed with a 100 ± 5 µL disposal micropipette (Brand, Wertheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test suspension was offered to the flies at a concentration of 8 mg protein mL −1 , while controls were fed with the desalted Adamek's liquid protein fraction. In either assay, the ingested volumes in controls and treatments were calculated by measuring the suspension remaining in each microtube cap 26. Every day for a 5 day period before refilling the caps, the suspension remaining in each cap was removed with a 100 ± 5 µL disposal micropipette (Brand, Wertheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In either assay, the ingested volumes in controls and treatments were calculated by measuring the suspension remaining in each microtube cap. 26 Every day for a 5 day period before refilling the caps, the suspension remaining in each cap was removed with a 100 ± 5 µL disposal micropipette (Brand, Wertheim, Germany). Three units without flies were run in parallel to monitor evaporation.…”
Section: Antifeedant Effects Of the Cspe Of Metarhizium Anisopliae Eamentioning
confidence: 99%
“…According to Edwards et al (2003) the increased consumption of the diluted product may result from the diluted product being easier to swallow. Nestel et al (2004) found that intake was signiÞcantly higher for low spinosad concentrations for both Dacus ciliatus Loew and C. capitata. This result was also observed when comparing a drop of fresh product with a drop of product after 24 h of application .…”
Section: Discussionmentioning
confidence: 97%
“…In all bioassays performed, adults of C. capitata were fed the toxic bait drops (40 μL) of the Success™ 0.02CB formulation, containing 96 mg L −1 of spinosad. This aspect is very important for the evaluation of the toxicity of formulations of toxic baits, as one of the main factors influencing the efficiency of the formulations is the phage-stimulating effect of the supplied material, which provides a greater or lesser attractiveness (Nestel et al 2004). Adults of C. capitata from larvae developed on artificial diet showed greater susceptibility to the Success™ 0.02CB toxic bait compared to insects from larvae developed in mango fruits, even though they had the same bait consumption.…”
Section: Discussionmentioning
confidence: 99%
“…For an ingestion experiment aimed at the evaluation of formulations of toxic baits, the longer the insect remains feeding and the greater the amount of food intake consumed, the greater the possibility of intoxication by the lethal agent and, consequently, the faster the effect of the product on the insect (Raga & Galdino 2018). Thus, the supply of another food source along with the toxic bait can reduce the consumption of the toxic bait and, consequently, the amount of lethal agent ingested by the insect (Nestel et al 2004, Raga & Galdino 2018. This fact may underestimate the lethal dose and the lethal time of the food attraction evaluated, especially if the insecticide does not present a knock-down effect, such as spinosad.…”
Section: Discussionmentioning
confidence: 99%